THE USE OF ICT IN MATHEMATICS CLASSES IN ELEMENTARY SCHOOL II - de Souza, Djair; Wendel Santana Coêlho, Márcio (Revista Gênero e Interdisciplinaridade, 2022)
This article aims to address how the use of modern technologies in the school context has provided several changes, it also brings the resistance of teachers in using technological means little, proposals and reflections about the use of innovative technologies in the teaching of mathematics in fundamental education II, within this modern model of Brazilian education. In this way, the use of ICTs as a pedagogical tool in the practice of teaching mathematics demonstrates that this teaching can be something attractive and creative as long as the teacher renews his teaching practice. Some reflections were made, and an attempt was made to understand the way in which teachers and students are dealing with these modern technological resources existing in the educational institution. It is important to highlight the theorists’ conceptions regarding the insertion of technologies in mathematics classes and within this context, attractive methods are sought for both teachers and students.